دَوْرُ العَرَبِيَّةِ اليَوْمِيَّةِ فِيِ تَحْسِيْنِ مَهَارَةِ المُحَادَثَةِ - Siti Nurparoh; Dzul Demuna Tiar Aprilia; Ahmadi Rojali (Reflection : Islamic Education Journal, 2025)
This paper discusses the role of Arabic in improving speaking skills, especially in the context of daily life. Arabic, which is recognized as the language of revelation in the Qur'an and Hadith, has learning objectives that include understanding Islamic teachings, mastering vocabulary, and effective communication skills. Arabic learning does not only focus on linguistic aspects, but also includes understanding the cultural and social norms that exist in Arab society. The scope of the role of everyday Arabic includes mastering basic vocabulary, improving practical communication skills, understanding simple grammatical structures, and adapting to dialects and cultural contexts. The benefits of learning Arabic are significant, including an understanding of religious teachings, increased educational and career opportunities, and the ability to establish cross-cultural social relationships. Effective learning methods, such as direct, grammatical-translational, and eclectic methods, are proposed to overcome the challenges faced in learning Arabic, such as the complexity of grammatical structures and the lack of exposure in Arabic-speaking environments. With the right strategy, Arabic language learning is expected to form individuals who are not only academically intelligent, but also have high integrity and religious awareness.